2020
DOI: 10.1021/acschembio.0c00581
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Transcription–Translation in One Approach for Activation of Cryptic Biosynthetic Gene Clusters

Abstract: The ever-growing drug resistance problem worldwide highlights the urgency to discover and develop new drugs. Microbial natural products are a prolific source of drugs. Genome sequencing has revealed a tremendous amount of uncharacterized natural product biosynthetic gene clusters (BGCs) encoded within microbial genomes, most of which are cryptic or express at very low levels under standard culture conditions. Therefore, developing effective strategies to awaken these cryptic BGCs is of great interest for natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Furthermore, we observed a starter unit‐dependent clade in the CLF trees. For example, murayaquinone [10] and piloquinone [11] have an identical polyketide scaffold, but the uncanonical isocaproyl‐CoA starter unit in piloquinone sets it apart from murayaquinone in the CLF tree (Figure S3). These results indicate that the phylogenetic cladogram of CLFs has a high correlation with the products’ chemical structures and their respective biosynthetic courses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we observed a starter unit‐dependent clade in the CLF trees. For example, murayaquinone [10] and piloquinone [11] have an identical polyketide scaffold, but the uncanonical isocaproyl‐CoA starter unit in piloquinone sets it apart from murayaquinone in the CLF tree (Figure S3). These results indicate that the phylogenetic cladogram of CLFs has a high correlation with the products’ chemical structures and their respective biosynthetic courses.…”
Section: Resultsmentioning
confidence: 99%
“…[27] B) HPLC analysis of the culture extract. C) Structure of WS-5995 D (9) and other known derivatives (10)(11)(12).…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Many methods were designed and employed to awaken expression of silent gene cluster (Alam et al, 2021;Ji et al, 2018;Luo et al, 2013;Wang et al, 2019;F. Xu, Nazari, et al, 2017;Q. Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although researches have shown that screening active ingredients from microbial metabolites [23] or translating antibacterial substances by transcription percentage of microbe cells, [24] is also effective ways to develop new antibiotics from natural microbial resources. However, compared with silver nanoparticles‐loaded polydopamine‐modified montmorillonite (AgNP/PDA−Mt), the preparation of the synthetic antimicrobial agent is simpler and more convenient.…”
Section: Introductionmentioning
confidence: 99%